Basic Profile of Early Childbirth in Nigeria - Malé, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of early childbirth in Nigeria. Measures of early childbirth are high. The share of women ages 18-22 who had their first child before 18 is 28.0 percent, but it has decreased over time. The share of women with their first child before 15 is at 5.1 percent. Early childbirth is associated with lower wealth and lower education levels, and employment with cash earnings. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.